Intraepithelial inclusions on urinalysis screening among COVID-19 cases: Are they covicytes?—A hospital-based cohort study with narrative review - Pushpanjali R Ojha; Rakesh Kumar (Journal of Cytology, 2024)
Title: “Intraepithelial inclusions on urinalysis screening among COVID-19 cases: Are they Covicytes?—A hospital-based cohort study with narrative review.” Context: Coronavirus disease 2019 (COVID-19)-associated delayed acute kidney injury (AKI) is often reported in subsequent waves of the pandemic. Early intervention and regular follow-up influence the outcome and inhibit progression into chronic kidney disease (CKD). This is the first study to identify urinary cytomorphological abnormalities (Covicytes) and predict COVID-19-associated delayed AKI with a narrative review of the possible etiologies for intraepithelial inclusions. Settings and Design: A hospital-based cohort study with a narrative review. Material and Methods: Screening urinalysis to assess the cytomorphology of epithelial cells (ECs) and inclusions in Leishman and periodic acid–Schiff (PAS)-stained smears by two independent pathologists was performed in reverse transcriptase polymerase chain reaction (RT-PCR)-confirmed COVID-19 cases at a tertiary care center. Statistical Analysis: Basic statistical tools were used for descriptive statistical analysis, and data were expressed in mean, proportion, and frequency. Results: Cytomorphological abnormalities (48/188) were predominant among adult males. Leukocyturia (39/48) with positive nitrite test (28/39), high ECs (27/48) and squamous cell-to-tubular EC (SC:TEC) ratio, intraepithelial intracytoplasmic inclusions predominantly in TECs (Covicytes), and multiple well-visualized, perinuclear PAS-negative neutrophilic vacuoles (17/39) were found. The association with preexisting diabetes (31/48), hypertension (10/48), and disease severity was noted. Conclusions: This study reported COVID-19-associated urinary cytomorphological abnormalities and interesting unique inclusions (Covicytes) that may be a result of underlying inflammatory changes, reactive hyperplasia, degenerative changes, or defective endocytosed vacuoles. The possible etiologies for renal inclusions were reviewed. We recommend compulsory baseline and follow-up urinary cytology screening for all COVID-19-suspected patients to detect and predict delayed AKI before clinical and biochemical manifestation during disease endemicity.